Mixed-Mating Model of Reproduction Revealed in European Phytophthora cactorum by ddRADseq and Effector Gene Sequence Data - Matěj Pánek; Ivana Střížková; Miloslav Zouhar; Tomáš Kudláček; Michal Tomšovský (Microorganisms, 2021)
A population study of Phytophthora cactorum was performed using ddRADseq sequence variation analysis completed by the analysis of effector genes—RXLR6, RXLR7 and SCR113. The population structure was described by F-statistics, heterozygosity, nucleotide diversity, number of private alleles, number of polymorphic sites, kinship coefficient and structure analysis. The population of P. cactorum in Europe seems to be structured into host-associated groups. The isolates from woody hosts are structured into four groups described previously, while isolates from strawberry form another group. The groups are diverse in effector gene composition and the frequency of outbreeding. When populations from strawberry were analysed, both asexual reproduction and occasional outbreeding confirmed by gene flow among distinct populations were detected. Therefore, distinct P. cactorum populations differ in the level of heterozygosity. The data support the theory of the mixed-mating model for P. cactorum, comprising frequent asexual behaviour and inbreeding alternating with occasional outbreeding. Because P. cactorum is not indigenous to Europe, such variability is probably caused by multiple introductions of different lineages from the area of its original distribution, and the different histories of sexual recombination and host adaptation of particular populations.